사이버공간과 『구운몽』의 세계 - 전이정(Yi-Jeong Jeon) (한국콘텐츠학회 논문지, 11(6), 2011)
The availability of computers and the wide network of the internet of the 'Information Society' has created a new space: Cyberspace. In this situations, the matters of individual identities and morality are more important problems. Korean classical novel, Gu Wun Mong, embodied the exploration process of identities in virtual spaces, has gravity of a situation. Seong Jin, the hero experienced the life of Yang so you went throughing virtual life, be born again. And he met eight taoist fairy in that virtual world. In this process, Seong Jin overcame a dualistic world of view and established identity of genuine truth-seeker. The 'Dream-fantasy' experience differentiation real world and virture world and give to Seong Jin a new identity, So You. Seong Jin used avatar, So You was free from limits of self and became obtain multiple personalities. Finally, Seong Jin realized the fact that real world and virtual one is the same, for development self-perception. Seong Jin's enlightment provided solutions for modern netizens, who is ambivalent about contradiction the real and virtual, infinity and clash of desire. 최근 통신 기술과 인터넷의 발달로 인해 현대인들의 활동영역이 사이버 공간으로 넓어지면서 사이버공간에서의 자아 정체성과 윤리 문제가 중요하게 부각되고 있다. 이러한 시점에서 가상공간에서의 환몽 체험을 통해서 진정한 자아를 탐색하는 과정을 담은 우리 고전 소설 구운몽 은 현대 네티즌들에게 의미있는 시사점이 될 수 있다. "구운몽"의 주인공인 성진은 환생을 통해서 또다른 욕망의 주체인 팔선녀와 만남으로써 가상 세계를 체험하고 있다. 이를 통해 성진은 '진/가'의 이원적인 세계관을 극복하고 진정한 구도자로서의 자아를 확립하기에 이른다. "구운몽"의 환몽 체험은 현실 세계와 가상 세계를 구별하면서, 성진에게 양소유라는 새로운 자아를 부여한다. 성진은 아바타인 양소유를 통해서 자아의 한계를 초월하여 다중적인 주체로서 자신을 자리매김한다. 이러한 주체의 확장을 통해 결국 성진은 현실과 가상이 모두 깨달음을 위한 주체의 통합 과정임을 인식하게 된다. 이렇듯, "구운몽"은 컴퓨터와 같은 물리적인 매개로서가 아니라 인간의 정신으로 구성되는 가상 체험, 가상 세계를 이야기하고 있는 작품으로 이해된다. 현실 세계와 가상 세계의 대립, 충돌과 욕망의 무한성 속에서 갈등하는 현대 네티즌들에게 자아에 관한 성진의 깨달음은 모순적인 상황을 해결할 수 있는 열쇠가 될 수 있을 것이다.